2022
DOI: 10.1055/a-1906-8000
|View full text |Cite
|
Sign up to set email alerts
|

Risk of residual neoplasia after a noncurative colorectal endoscopic submucosal dissection for malignant lesions: a multinational study

Abstract: Background and study aims: Endoscopic submucosal dissection (ESD) in colorectal lesions is technically demanding, and a significant rate of non-curative procedures is expected. We aimed to assess the rate of residual lesion after a non-curative ESD for colorectal cancer (CRC), and to establish predictive scores to be applied in the clinical setting. Patients and Methods: Retrospective multicenter analysis of consecutive colorectal ESDs. Patients with non-curative ESDs performed for the treatment of CRC lesions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…Lesion recurrence (or residual neoplasia) after ESD can occur and is influenced by several factors. Primarily, piecemeal resection, poor differentiation, and positive/indeterminate vertical margin have been identified as the strongest risk factors in a recent large multicenter analysis[ 24 ]. While overall follow up rates were low, we found no significant association between cirrhosis and disease recurrence after multivariate analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Lesion recurrence (or residual neoplasia) after ESD can occur and is influenced by several factors. Primarily, piecemeal resection, poor differentiation, and positive/indeterminate vertical margin have been identified as the strongest risk factors in a recent large multicenter analysis[ 24 ]. While overall follow up rates were low, we found no significant association between cirrhosis and disease recurrence after multivariate analysis.…”
Section: Discussionmentioning
confidence: 99%
“…In summary, the results of the study by Santos-Antunes et al [1] on the risk of lymph node metastasis should be interpreted with great caution. In our experience, in a large cohort of patients with long-term follow-up data, pT1b (sm2) still results in an elevated risk of LNM even without other poor prognostic factors, and complementary surgical resection should be recommended in patients who are good candidates for surgery.…”
mentioning
confidence: 88%
“…The multicenter study of colorectal endoscopic submucosal dissection (ESD) in the West, reported by Santos-Antunes et al 1 , showed that the risk factors for the presence of residual lesions in the wall were piecemeal resection, poor differentiation, and positive or indeterminate vertical margin. pT1b cancers (invasion deeper than 1000 μm from the muscularis mucosae) without any other risk factors did not present with residual lesions during the follow-up period.…”
mentioning
confidence: 99%
“…However, these different risk criteria do not have the same impact on the lymph node prognosis of these lesions. Some recent data show that the histological criterion of submucosal invasion depth<1000µm may not be an independent risk criterion for lymph node metastasis 3 , and the risk associated with it seems low 4 . The aim of this study was to evaluate the risk of lymph node metastasis or recurrence in cases of endoscopic resection with or without complementary surgery of T1 colorectal cancer with submucosal invasion of more than 1000 µm and without any other pejorative histological factors.…”
mentioning
confidence: 99%